Batas Tanggung Jawab PPAT dalam Pembuatan Akta Tanah Berdasarkan Pengecekan Sertipikat Elektronik yang Mengandung Kesalahan - Rosalina Putri Robin; Ni Putu Rai Yuliartini; Rimah Afsari (JURNAL ILMIAH NUSANTARA, 2026)
The digitalization of land services through the implementation of an electronic certificate checking system by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) aims to enhance legal certainty in land deed preparation. However, inaccuracies in the electronic system may raise legal issues concerning the liability of Land Deed Officials (PPAT). This study aims to analyze the legal framework governing the use of electronic certificate checking and the limits of PPAT's liability when the system contains inaccurate data. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that electronic certificate checking serves as an administrative verification instrument rather than an integral part of or a validity requirement for a land deed. A PPAT who has complied with all applicable procedures cannot be held liable for inaccuracies originating from the ATR/BPN electronic system, whereas a negligent PPAT remains legally responsible. Therefore, clearer regulations are needed to ensure legal certainty regarding the allocation of liability for inaccuracies in the electronic land administration system.